Anosognosia and schizophrenia – a reminder. (June 2021) - Little, John D; Bell, Elliot
Objective: To remind the clinical and legal practitioner that anosognosia is a recognised facet of schizophrenia with implications for capacity assessment and for relating effectively with people who experience it. Conclusions: The term anosognosia emphasises that, in schizophrenia, lack of capacity is the result of a neurological deficit. Under-appreciation of this may place that person at risk of a preventable harm.